Like a duck to water: Do credit rating analysts outperform in bond fund management - Hu, Xiaolu; Luo, Haoyi (Journal of Corporate Finance, 2023)
This paper investigates whether bond fund managers with credit rating experience outperform their peers. We document that bond fund managers who previously worked in credit rating agencies on average create higher risk-adjusted returns than their peers by 11–16 bps per month, with better security picking and market timing skills. We further confirm that this outperformance is sourced from their industry-specific knowledge gained via rating experience (specialization), rather than information advantage provided by previous colleagues (network). Last, we document net inflows to funds managed by agent managers, indicating the investor awareness of analyst managers' skill.